Meningkatkan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Creative Problem Solving (CPS) Pada Tema 8 Lingkungan Sahabat Kita - Oktavia Natalia Sinaga; Dewi Anzelina; Bogor Lumbanraja; Patri Janson Silaban; Antonius Remigius Abi (Departement of Mathematics Education, 2023)
The most fundamental principle of Curriculum 13 is the emphasis on the ability of teachers to implement an authentic, challenging and meaningful learning process for students so that the potential of students can develop in accordance with what is expected by the objectives of national education. However, there are still many teachers who cannot or are still confused in implementing or implementing the 2013 Curriculum in learning. So that learning has meaning, teachers must have skills in teaching both skills in applying learning models and learning media that are close to the students' environment. As for what can be done so that the learning process is fun and can improve learning outcomes and the activeness of students in expressing opinions and asking questions related to the teaching material presented, the right model is needed in the learning process. There is a learning model that can be used in the learning process, namely the Creative Problem Solving (CPS) learning model. Based on the analysis and discussion of the results of research conducted in the VA class of SD St. Thomas 5 Medan in the 2022/2023 learning year, it can be concluded that the implementation of learning by using the Creative Problem Solving learning model on the theme of Our Friends Environment with the sub-theme of Humans and the Environment in the VA class of SD St. Thomas 5 Medan in the 2022/2023 learning year is categorized as good. it can be seen from the results of students’ learning outcome improvement in cycle I obtained as much as 68% of the good category and in cycle II it increased to 90% of the very good category.